2016
DOI: 10.1002/2016jc011736
|View full text |Cite
|
Sign up to set email alerts
|

CMIP5 earth system models with biogeochemistry: An assessment for the southwest Pacific Ocean

Abstract: An assessment is made of the ability of CMIP5 models to represent the seasonal biogeochemical cycles over the late twentieth century in the southwest Pacific Ocean. In particular, sea surface temperature (SST), surface chlorophyll a, nitrate, phosphate, silicate, and the depth of the seasonal thermocline, are examined to quantify the physical‐biogeochemical capabilities of each model; the result is a “ranking” estimate enabling model ensemble generation. The better/less ranked ensembles we refer to as inner/ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 44 publications
5
44
0
Order By: Relevance
“…Firstly, the two values for the elemental composition at the average present-day conditions and the projected conditions for the year 2100 were derived from each fitted dose-response curve for the environmental driver that had significant effects. The environmental conditions were projected using Coupled Model Intercomparison Project phase 5 (CMIP5) models (Boyd and Law, 2011;Law et al, 2016;Rickard et al, 2016), which suggested 33 % decreases in both nitrate and phosphate concentrations, 2 • C warming, a 25 % increase in irradiance, and an increase in pCO 2 from 39 to 75 Pa in the Chatham Rise area for the year 2100 compared to present-day conditions (Feng et al, 2017). The magnitude and direction of percentage change in the elemental composition under projected future conditions relative to the presentday condition for each environmental driver was then calculated.…”
Section: Data Analysesmentioning
confidence: 99%
“…Firstly, the two values for the elemental composition at the average present-day conditions and the projected conditions for the year 2100 were derived from each fitted dose-response curve for the environmental driver that had significant effects. The environmental conditions were projected using Coupled Model Intercomparison Project phase 5 (CMIP5) models (Boyd and Law, 2011;Law et al, 2016;Rickard et al, 2016), which suggested 33 % decreases in both nitrate and phosphate concentrations, 2 • C warming, a 25 % increase in irradiance, and an increase in pCO 2 from 39 to 75 Pa in the Chatham Rise area for the year 2100 compared to present-day conditions (Feng et al, 2017). The magnitude and direction of percentage change in the elemental composition under projected future conditions relative to the presentday condition for each environmental driver was then calculated.…”
Section: Data Analysesmentioning
confidence: 99%
“…Few fully resolved annual cycles in carbonate system chemistry exist for the Southern Ocean (Munro et al, ; T14) and even the most realistic Earth system models tend to both be biased (Law et al, ; Rickard et al, ) and to underestimate the seasonal cycles in carbonate system parameters (Sasse et al, ) as compared to recent observational time series data. This is because data sets that do exist are often biased toward summer and coastal data (Jones et al, ; McNeil et al, ; Roden et al, , ; Shadwick et al, ) or are heavily weighted toward data from the Drake Passage region (Munro et al, ; Sprintall et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The SST and microfossil assemblage results from the transect of cores show that warming during the early Holocene climatic optimum is not spatially uniform across the midlatitudes of the SW Pacific (Prebble et al, 2017). However, these SST spatial variations experienced in the early Holocene closely resemble the future SST pattern from combined ESMs, which show the greatest warming in the STW to the north along the TF, and another patch of greater warming extending over, and south of, Chatham Rise, and less warming in the SAW and little to no warming south of the PF (Law et al, 2017;Rickard et al, 2016). The early Holocene SST changes, however, are significantly lower than those estimated for the end of the century (2100 AD) for RCP8.5 and are closer to those suggested for midcentury (2055 AD) for RCP8.5 or end of the century (2100 AD) for RCP4.5 (Rickard et al, 2016).…”
Section: Analog For Productivity Changes In a Warmer World?mentioning
confidence: 67%
“…Under the RCP4.5 2100 and RCP8.5 2055 scenarios, the ESMs predict relatively small declines in the surface nutrients and chlorophyll a and a significant small decrease in integrated primary productivity in the STW in the SW Pacific (Rickard et al, ). This contrasts with the evidence for a slight increase in “productivity” (from increased CMAR, OMAR, δ 15 N bulk , and alkenone concentrations) in the STW cores during the early Holocene in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation